2021
DOI: 10.1017/jfm.2021.164
|View full text |Cite
|
Sign up to set email alerts
|

Thermal capillary wave growth and surface roughening of nanoscale liquid films

Abstract: Abstract

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 40 publications
3
32
0
Order By: Relevance
“…The resulting van der Waals forces can be either attractive or repulsive. In the case of attractive interactions, the fluctuations are amplified by intermolecular forces and the film is predicted to be unstable [13][14][15][16]. This is confirmed by experimental observations on dewetting polymer films of nanometric thickness [7].…”
supporting
confidence: 60%
“…The resulting van der Waals forces can be either attractive or repulsive. In the case of attractive interactions, the fluctuations are amplified by intermolecular forces and the film is predicted to be unstable [13][14][15][16]. This is confirmed by experimental observations on dewetting polymer films of nanometric thickness [7].…”
supporting
confidence: 60%
“…It was shown that thermal noise changes the spectrum of thermal capillary waves from an exponential decay to a power law for large wavenumbers, which was then confirmed by the experimental observations on the dewetting of polymer films [18]. The same behaviour of spectrum was also confirmed in MD simulations, first done by Willis & Freund [19] in 2010 and recently, followed by Zhang et al [20], who showed that interfacial roughening falls into a universality class [11]. However, theories based on small deviations from equilibrium cannot, inevitably, describe inherently nonlinear events such as film breakup.…”
Section: Introductionmentioning
confidence: 53%
“…The fluctuations of the interface in thermal equilibrium [11,17] can be described by the classical theory for thermal capillary waves [7,18] with the static spectra of each surface mode (wavenumber) derived from the equipartition theorem. To capture the development of thermal capillary waves towards the equilibrium state, more advanced theories that include the time evolution of wave spectra were derived by applying linear stability analysis to the SLE [20,22]; we will use the model from Ref.…”
Section: Numerical Verification: Thermal Capillary Wavesmentioning
confidence: 99%
See 1 more Smart Citation
“…Scaling relations are found for the process of surface roughening and the time scale for a smooth surface to reach thermal equilibrium is extracted. 19 When in thermal equilibrium, it is well known that the temporal correlations of surface modes show an exponential decay, with a decay rate given by the dispersion relation of the system. Based on this, X-ray Photon Correlation Spectroscopy (XPCS) or similar techniques, can be used to infer the features of liquid-solid systems such as surface tension, viscoelasticity, and substrate surface structures.…”
Section: Introductionmentioning
confidence: 99%